2008
DOI: 10.1055/s-2008-1075614
|View full text |Cite
|
Sign up to set email alerts
|

Megacystis-Microcolon-Intestinal Hypoperistalsis Syndrome in a Newborn After Clomiphene Ingestion During Pregnancy

Abstract: A case of megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) in a newborn after clomiphene ingestion during pregnancy is described. Review of the literature revealed no other MMIHS associated with maternal clomiphene ingestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…A review of the literature showed that 75 cases of MMIHS have been reported to date. (1‐27,28‐54) These cases were seen in 61 female and 14 male infants (ratio 4:1). In 2 cases pregnancy was terminated after ultrasonography detected the syndrome, which was confirmed at autopsy in both cases (34,36).…”
Section: Clinical Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…A review of the literature showed that 75 cases of MMIHS have been reported to date. (1‐27,28‐54) These cases were seen in 61 female and 14 male infants (ratio 4:1). In 2 cases pregnancy was terminated after ultrasonography detected the syndrome, which was confirmed at autopsy in both cases (34,36).…”
Section: Clinical Materialsmentioning
confidence: 96%
“…The maternal age ranged from 18 to 36 years (mean 27 years). In 2 patients, exposure to drugs (clomiphene [31], scopolamine, trimethoprim‐sulfadiazine, and dypirone [41]) during the first weeks of gestation was reported.…”
Section: Gestation and Deliverymentioning
confidence: 99%
“…Hastalığın 1976 yılında tanımlanmasından sonra patogenezinin açıklanması için, genetik, nörojenik, miyojenik, hormonal ve toksik teoriler ortaya atılmıştır (2,(13)(14)(15)(16)(17) . Puri ve ark.…”
Section: Patogenezunclassified
“…En sık rastlanan bulgu prenatal ultrasonografide (USG) büyümüş mesane ve hidronefrozdur (2,13) . Kli- nik tablo diğer bütün ağır yenidoğan bağırsak tıkanıklıkları tabloları ile benzerlik gösterir.…”
Section: Klinik Bulgularunclassified